2023
DOI: 10.1093/oncolo/oyad053
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Treatment Sequencing on Overall Survival in Patients with Transplant-Ineligible Newly Diagnosed Myeloma

Abstract: Background Because patients with newly diagnosed multiple myeloma (NDMM) do not always receive any treatment beyond first-line (1L) therapy, it is imperative that patients receive the best treatment in the 1L setting. However, the optimal initial treatment remains to be identified. We performed a clinical simulation to assess potential outcomes with different treatment sequences. Patients and Methods We used a partitioned sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Moreover, a higher probability of being alive at 5, 10, and 15 years was associated with first-line D-Rd, as compared with first-line VRd or Rd. These data suggest the importance of first-line therapy and confirm that achieving the longest possible PFS in first-line therapy drives survival outcomes [53].…”
Section: First-line Treatment For Transplant-ineligible Patients With...mentioning
confidence: 55%
“…Moreover, a higher probability of being alive at 5, 10, and 15 years was associated with first-line D-Rd, as compared with first-line VRd or Rd. These data suggest the importance of first-line therapy and confirm that achieving the longest possible PFS in first-line therapy drives survival outcomes [53].…”
Section: First-line Treatment For Transplant-ineligible Patients With...mentioning
confidence: 55%
“…According to Fonseca et al, it has been demonstrated that a DARA-containing regimen applied as the initial treatment leads to a longer median OS compared to introducing a DARA-containing regimen as a secondary treatment following VRd or Rd [ 46 ]. In the absence of head-to-head trials comparing D-Rd to VRd or to BTZ and DEX (Vd), the PEGASUS study compared PFS in patients treated with D-Rd in the MAIA trial and patients treated with common standard-of-care regimens from the Flatiron Health electronic health record-derived deidentified database [ 47 ].…”
Section: Frailty and Geriatric Assessmentmentioning
confidence: 99%
“…Over the past 40 years, multiple myeloma (MM) has evolved from an acute disease with a median overall survival (OS) of only ~3–4 years [ 1 ] to become a chronic disease in which the median OS is now 7–10 years [ 2 , 3 ], and patients can require multiple lines of therapy over their disease course [ 4 , 5 , 6 , 7 ]. In the context of a global annual incidence of approximately 180,000 new cases [ 8 ], including more than 35,000 in the United States alone [ 9 ], and the continuing increase in survival rates [ 10 ], there is a growing population of patients requiring additional treatment options.…”
Section: Introductionmentioning
confidence: 99%